Various technique of cell culture and slide preparation for human chromosome (Sirte Journal of Medical Sciences, 2022)
The cell culture and slide preparation method of human chromosome is the mechanism that is a corresponding change in DNA content. In this research we used various techniques of cell culture and slide preparation for human chromosome and examined for 2 days, 3 days and 4 days cell culture because these are average days for approximately the good results and the treatment will still be good also the result has minimum bias.The research objectives were to determine the appropriate length of cell culture needed for human chromosome with different lengths and to determine the appropriate method for staining the slide for human chromosome with different lengths.Based on the data analysis, the result of this research shows that the appropriate length of cell culture needed for human chromosome with different lengths is 2 days of incubation. Although there were no significant differences between 2,3 and 4 days length based on statistical analysis, still there is little difference between them and the best is 2 days rather than 3 and 4 days based on the graph analysis. The appropriate method for staining the slide for human chromosome with different lengths is hot plate rather than another technique